Prototype of the gas chromatograph–mass spectrometer to investigate volatile species in the lunar soil for the Luna-Resurs mission. (June 2015) - Hofer, L.; Wurz, P.; Buch, A.; Cabane, M.; Coll, P.; Coscia, D.; Gerasimov, M.; Lasi, D.; Sapgir, A.; Szopa, C.; Tulej, M.
Abstract: In preparation for the Russian Luna-Resurs mission we combined our compact time-of-flight mass spectrometer (TOF-MS) with a chemical pre-separation of the species by gas chromatography (GC). Coupled measurements with both instruments were successfully performed with the prototype of the mass spectrometer and a flight-like gas chromatograph. The system was tested with two test gas mixtures, a mixture of hydrocarbons and a mixture of noble gases. Due to its capability to record mass spectra over the full mass range at once with high sensitivity and a dynamic range of up to 10 6 within 1 s, the TOF-MS system is a valuable extension of the GC analytical system. Based on the measurements with calibration gases performed with the combined GC–MS prototype and under assumption of mean characteristics for the Moon's regolith, the detection limit for volatile species in a soil sample is estimated to 2·10 −10 by mass for hydrocarbons and 2·10 −9 by mass for noble gases. Highlights: Development of a sensitive GC-MS instrument for in situ measurements on the Moon. GC-MS coupling with a time-of-flight type mass spectrometer. Prototype measurements with noble gases and hydrocarbons.